PERAN MODERASI KOMITMEN AFEKTIF PADA PENGARUH KETIDAKAMANAN KERJA TERHADAP NIAT UNTUK KELUAR - Astutik, Sri; Partina, Anna; Pratikna, Rizka Nugraha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025, 2025)
The increasing competitiveness in business and digitization have driven firms to embrace outsourcing as a method for efficiency and human resource management. Outsourced employees frequently suffer employment uncertainty, affecting their motivation to leave the firm. This study intends to evaluate the impact of work insecurity on turnover intention, with affective commitment serving as a moderating variabel. Resource conservation underpins the study. This quantitative analysis encompassed 81 outsourced employees from PT X in the Special Region of Yogyakarta. Data were gathered by surveys employing a Likert scale and analyzed utilizing WarpPLS. The findings demonstrate that work uncertainty significantly increases turnover intention. Affective commitment was identified as a negative moderator of the link between work insecurity and turnover intention, indicating that the impact of job insecurity diminishes when affective commitment is elevated. This study enhances conservation of resources theory by emphasizing the role of affective commitment in mitigating employment volatility. The results suggest that outsourcing companies should improve affective engagement to reduce turnover.